Arbitration agrement and standard form contracts: judgement number 409/2017 of 27th june of the Spanish Supreme Court - Blanco García, Ana Isabel; Quinzá Redondo, Pablo (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Judgment number 408/2017 of the Spanish Supreme Court deals with the potential application of an arbitration agreement in the case of a standard form contract. In particular, it focuses on the jurisdiction of the judge to interpret the arbitration agreement and on the questions that are covered by the arbitration agreement itself.
Keywords: arbitration; standard form contract; arbitration agreement